Complementarity of Buddhist Denominations - Kochumuttom, Thomas (Journal of Dharma, 1987)
The present author believes that it is only by a process of branching out a movement can develop. This applies also to religions. By ’a process of branching out’ I do not mean merely the multiplication of religious institutes, but even the diversification of the views and interpretations of the same faith. A religion branches out by encouraging a plurality of views and interpretations of its faith-content. For an impartial observer a new view or interpretation, even if it is perfectly in tune with the orthodox position, may appear to the well-intentioned traditionalists to be a threat to the unity of faith. This can happen even in the case of merely administrative or other functional divisions of a religion, which in fact only serves to assist its expansion. I know of a Catholic religious congregation in this country which bad to face tremendous opposition from its own members when it was proposed to be divided into provinces for administrative convenience. However, even those who were opposed to the idea of division would have to accept that for the congregation to grow in number and achieve efficiency in its undertakings, such a division was inevitable. Even so they felt that the unity of the congregation was at stake. This was obviously an un- warranted fear generated by a false idea of unity. If the question of a merely administrative division can cause pain, then that of a doctrinal and disciplinary division of a religion, however legitimate it may be, will be much more painful to the conscientious members. It is indeed the birth- pang, and, therefore, to be welcomed as it will bring new life and vigour.